2019
DOI: 10.1142/s0219887820500127
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate points for systems of second-order ordinary differential equations

Abstract: We recall the notion of Jacobi fields, as it was extended to systems of second-order ordinary differential equations. Two points along a base integral curve are conjugate if there exists a non-trivial Jacobi field along that curve that vanishes on both points. Based on arguments that involve the eigendistributions of the Jacobi endomorphism, we discuss conjugate points for a certain generalization (to the current setting) of locally symmetric spaces. Next, we study conjugate points along relative equilibria of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In [11], we have shown that the existence of the parallel vector field in part (2) of Proposition 1 can be guaranteed by requiring the condition [∇Φ, Φ] = 0 on the spray. When restricted to an eigendistribution of Φ, this condition can be characterized as follows.…”
Section: The Bracket Propertymentioning
confidence: 99%
See 3 more Smart Citations
“…In [11], we have shown that the existence of the parallel vector field in part (2) of Proposition 1 can be guaranteed by requiring the condition [∇Φ, Φ] = 0 on the spray. When restricted to an eigendistribution of Φ, this condition can be characterized as follows.…”
Section: The Bracket Propertymentioning
confidence: 99%
“…In view of the first condition in Proposition 1, we may reach an even simplier expression if λ is a first integral of S. If that is the case, all geodesics are constant along λ and the factor − S(λ+a) λ+a + P simplifies to −4P + P = −3P . For instance, locally symmetric sodes fall into that category (see [11], Section 5 for details). The condition on the projective factor that guarantees this property can be calculated as follows.…”
Section: The Bracket Propertymentioning
confidence: 99%
See 2 more Smart Citations